Duszpasterstwo osób żyjących w małżeństwie i rodzinie według wybranych dyrektoriów. Aspekt prawno-duszpasterski - Adamczyk, Jerzy (Ius Matrimoniale, 2017)
The following article is devoted to people living in marriage and family according to some directories in the legal-priestly aspect. Firstly, the definition and the need for family ministry was presented. Secondly, the evangelization of marriages and families was presented, as well as the issue of serving life and helping families. The final part of the presentation discusses the problem of family ministry in special circumstances.